2023
DOI: 10.1007/s10687-022-00460-8
|View full text |Cite
|
Sign up to set email alerts
|

A combined statistical and machine learning approach for spatial prediction of extreme wildfire frequencies and sizes

Abstract: Motivated by the Extreme Value Analysis 2021 (EVA 2021) data challenge we propose a method based on statistics and machine learning for the spatial prediction of extreme wildfire frequencies and sizes. This method is tailored to handle large datasets, including missing observations. Our approach relies on a four-stage high-dimensional bivariate sparse spatial model for zero-inflated data, which is developed using stochastic partial differential equations (SPDE). In Stage 1, the observations are categorized in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…We also found that for the non-missing CNT and BA observations, the probability of observing a zero observation exceeded 0.999 for both variables when lc (18) i > 0.94 , where lc (18) i denotes the proportion of each location covered by water. Therefore, for any i ∈ CNT val ( i ∈ BA val ) with lc (18)…”
Section: Exploiting Features Of the Missing Datamentioning
confidence: 69%
See 1 more Smart Citation
“…We also found that for the non-missing CNT and BA observations, the probability of observing a zero observation exceeded 0.999 for both variables when lc (18) i > 0.94 , where lc (18) i denotes the proportion of each location covered by water. Therefore, for any i ∈ CNT val ( i ∈ BA val ) with lc (18)…”
Section: Exploiting Features Of the Missing Datamentioning
confidence: 69%
“…For example, [15] show that the Forest Fire Danger Index, typically used in Australia, is inadequate for predicting the behaviour of moderate to high-intensity wildfires. Machine learning techniques have also been adopted for wildfire modelling: [16] and [17] use deep learning techniques; [18] present a four-stage process including a random forest algorithm; and [19] develops a gradient boosting model trained with loss functions appropriate for predicting extreme values. We take a simpler, marginalbased approach.…”
Section: Existing Methodsmentioning
confidence: 99%